Does Vaccinations Reduce the COVID-19 Infection? - Fujita, Yasunori (Archives of Business Research, 2021)
Since the outbreak of COVID-19, each government has been struggling to find the ways of fighting off the coronavirus, with the vaccination being one of the most promising ways of doing it. In Japanese also, the government has started administering the vaccinations to the general public and is now analyzing the data from the recipients. In the present paper, we investigate the vaccine's efficacy by building a simple intertemporal theoretical model. Main result we obtain is that administering the vaccinations can increase number of the infected individuals, contrary what is widely believed.